EATING BROADCAST: A QUALITATIVE ANALYSIS OF MUKBANG CONSUMPTION AND ITS SOCIO-CULTURAL AND PSYCHOLOGICAL IMPLICATIONS IN TAMIL NADU. - S, Sherlin Suji; Raja, G. Balasubramania (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The emergence of Mukbang also known as eating broadcast, a unique form of digital content in which individuals consume large quantities of food while broadcasting live or recorded and posted on social media platforms. It has been rapidly gaining popularity among young individuals, particularly in Tamil Nadu. This study aimed to investigate the socio-cultural implications of mukbang consumption in Tamil Nadu, focusing on the reasons behind its widespread popularity and its impact on the minds and health of young people. Through a qualitative analysis of fifteen mukbang videos from popular hosts and in-depth interviews with six participants, the study revealed that Mukbang videos often feature a diverse range of food items, recurring themes presentation styles, and the researcher found the dominant characteristics within the mukbang genre. The in-depth interviews also identified several behavioural outcomes among youth from watching Mukbang videos. The findings underscore the importance of understanding the cultural, social, and psychological factors that influence an individual’s media consumption habits and their relationship with food.